Strength and conditioning practices of high school rugby coaches: a South African context - Robinson, Bradley Charles (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2018)
Although the sport of rugby union is well established, the strength and conditioning practices of high school level players are not well known. Therefore, the purpose of this study was to examine the current strength and conditioning practices that coaches implement at South African high school level rugby. A secondary purpose was to compare practices between different types of schooling systems available in South Africa. An online survey or in person interview (depending on the school), adapted from previous strength and conditioning questionnaires, was conducted with 43 responses; including 28 schools among the top 100 rugby schools in South Africa for 2016 and 15 no-fee paying public schools in the Eastern Cape Province of South Africa. Results indicated that the top 100 rugby schools implement conditioning practices similar to the best-known international practices compared to no-fee paying schools who lacked the knowledge and skills in various strength and conditioning principles. It was found that all no-fee paying school coaches had insufficient qualifications to administer the correct training techniques. Coaches at all schools lacked the appropriate knowledge on injury prevention and scientifically based training programmes. It was concluded that education and skills around the best strength and conditioning practices for school level coaches needs to be improved and particularly in less privileged schools. The main goal being to reduce the risk of injury and improve performance across all sectors of the rugby playing population within the country. This was deemed crucial to the transformation goals set out by the South African Rugby Union, which would benefit from player development in lower socioeconomic schools.
Keywords: Rugby football coaches -- South Africa; Rugby football Coaching; Rugby football Physiological aspects; Rugby football Training; High school students Social conditions